KESANTUNAN BERBAHASA DALAM ANTOLOGI CERPEN DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI SMA - Syamsul Anwar, dan Agus Riyanto, Maedi Adi Saputro, (Sasando, 2022)
The purpose of this research; describes the politeness of the language used in the short story Anthology of Tembang Talijiwo by Sujiwo Tejo and describes the implications of research results on Indonesian language learning in high school. This study used descriptive qualitative method. The data source of this research is the short story anthology of Tembang Talijiwo by Sujiwo Tejo. The form of this research data is in the form of sentence fragments and conversations in the book Tembang Talijiwo. The technique of providing data in this study used the listening method and note-taking technique. The data analysis technique used a descriptive analysis study. The technique of presenting the results of data analysis uses informal techniques. The results of the study show politeness in the language contained in the short story Anthology of Tembang Talijiwo by Sujiwo Tejo with a total of 20 data. This politeness research is implicated in learning Indonesian in high school at basic competence 4.8 is Demonstrating one of the values ​​of life learned in short stories in class XI semester 2 Keywords: politeness of language, short story anthology and its implementation